Exaggerated Pressor Response in Relation to Attenuated Muscle Temperature Response during Contraction in Ischemic Heart Failure - Li, Jianhua; Gao, Zhaohui; Lu, Jian; Xing, Jihong (Frontiers in Physiology, 2012)
It is known that muscle temperature (Tm) increases with exercise. The purpose of this study was to examine if contraction-induced increase in Tm was altered in rats with heart failure (HF) induced by chronic myocardial infraction (MI) as compared with healthy control animals. A temperature probe was inserted in the triceps surae muscle to continuously measure Tm throughout experiments. Static muscle contraction was induced by electrical stimulation of the sciatic nerve for 1 min. As baseline Tm was 34°C, contraction increased temperature by 1.6 ± 0.18°C in nine health control rats and by 1.0 ± 0.15°C in 10 MI rats (P < 0.05 vs. control). Note that there were no differences in developed muscle tension and muscle weight between the two groups. In addition, muscle contraction increased mean arterial pressure by 23 ± 3 mmHg in control rats and by 31 ± 3 mmHg in MI rats (P < 0.05 vs. control). A regression analysis further shows that there is an inverse liner relationship between the pressor response and static contraction-induced increase in Tm. Our data suggest that Tm increase evoked by contraction is impaired in MI rats. The abnormal alteration in Tm likely modifies the reflex cardiovascular responses in MI via mechanisms of temperature-sensitive receptors on muscle afferent nerves.